Indonesia Prevalensi dan Komponen Sindrom Metabolik pada Pekerja Pria di Indonesia - Leli Hesti Indriyati; Irena Ujianti; Betty Semara Lakhsmi (Majalah Kedokteran Indonesia, 2023)
Introduction : Metabolic syndrome (MetS) has emerged as one of the world’s major public health issues and the prevalence of this syndrome varies among population. There is a little of information on the epidemiology of MetS in male workers in Indonesia. Therefore, this study aims to determine the prevalence, its component and risk factors of MetS in Indonesian’s male working population. Methods : This was a cross sectional study of 1298 workers (median age, IQR 41,37-48 years) who underwent a routine Medical Check Up (MCU). The metabolic syndrome is diagnosed using the criteria established by the revised National Cholesterol Education Program-Adult Treatment Panel-III definition (2005 ATP III). Results : Metabolic syndrome prevalence was 13.9% in male workers. The most common abnormalities among all participants were hypertriglyceridemia (94.5%) and abdominal obesity (80.6%) [p less than 0.001]. Multivariable logistic regression analysis revealed that obesity (OR: 9.29; 95% CI: 5.56-15.54), overweight (OR: 2.15; 95% CI: 1.11-4.18), increasing age (OR: 2.39; 95% CI: 1.36-4.21), white blood cells/WBC or leukocyte (OR: 1.13; 95% CI: 1.04-1.24) and exercise (OR: 1.51; 95% CI: 1.06-2.15), were associated with a higher risk of developing MetS in the working population. Conclusion : The most common component of MetS in workers is hypertriglyceridemia followed by abdominal obesity. As a result, it is possible that these are the first detectable component of MetS in the working population. Early detection of MetS components, especially in obese workers, could be effective way to prevent the development of the syndrome.